2012
DOI: 10.2527/jas.2012-5100
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene and protein expression of glucose transporter1 underlies dexamethasone inhibition of insulin-stimulated glucose uptake in chicken muscles1

Abstract: A study was performed to characterize the effects of dexamethasone (DEX) and insulin administration on gene expression of glucose transporters (GLUT) in chicken (Gallus gallus domesticus) skeletal muscles and in cultured embryonic myoblasts. Three groups of 1-wk-old male chickens were randomly subjected to one of the following treatments for 7 d: DEX (a subcutaneous injection of 1 mg/kg BW, twice daily at 0800 h and 2000 h), controls (injected with saline), and pair-fed controls (restricted to the same feed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Plasma insulin concentrations were also significantly decreased by fasting (Table 2). Zhao et al (2012) reported that GLUT1 mRNA levels were decreased by food restriction in the pectoralis major muscle and that insulin significantly increased the expression of GLUT1 in an in vitro study using chicken embryonic myoblasts. Therefore, these findings suggest that GLUT1 expression may be regulated by insulin in glycolytic type IIB fibers in chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma insulin concentrations were also significantly decreased by fasting (Table 2). Zhao et al (2012) reported that GLUT1 mRNA levels were decreased by food restriction in the pectoralis major muscle and that insulin significantly increased the expression of GLUT1 in an in vitro study using chicken embryonic myoblasts. Therefore, these findings suggest that GLUT1 expression may be regulated by insulin in glycolytic type IIB fibers in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GLUT1, GLUT3, and GLUT8 are expressed in chicken skeletal muscle, whereas the GLUT4 gene is absent in chicken genome (Kono et al, 2005;Seki et al, 2003). GLUT1 mRNA levels, but not those of GLUT3 and GLUT8, were previously reported to be decreased in the pectoralis major muscle by restricted feeding (Zhao et al, 2012). PFK-M and PFK-L (liver type) are expressed in the skeletal muscle of chickens (Seki et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Chicken GLUT1 shares 80% amino acid residues with humans [17]. Chicken GLUT1 has ubiquitous expression, with abundant expression in the hypothalamus, and has demonstrated response to insulin and dexamethasone [18]. According to NCBI Gene Database, GLUT1/SLC2A1 orthologs are conserved in 124 organisms including human, chicken, chimpanzee, cow, mouse, rat, Rhesus monkey, zebrafish and Eremothecium gossypii (fungus).…”
Section: Class I Glutsmentioning
confidence: 99%
“…Chicken GLUT3 shares 70% sequence similarity with the human's [25,2] and is known to be a neuronal glucose transporter [25]. The neuronal functions of GLUT1 and GLUT3 are similar across chickens and mammals [17,18]. In chickens, the upregulation of GLUT1 and GLUT3 is associated with the formation of tight junctions in the blood-retinal barrier [26].…”
Section: Class I Glutsmentioning
confidence: 99%
See 1 more Smart Citation